Surgery combined with anlotinib for local control of patients with resectable extremity desmoid fibromatosis: a retrospective study - Yuan, Dechao; Liu, Yong; Fang, Xiang; Wu, Fan; Lei, Senlin; Tu, Linqi; Kuang, Fuguo; Gou, Yawei; Gong, Chunfu; Zhang, Wenli; Duan, Hong (Frontiers in Pharmacology, 2024)
Background: Desmoid fibromatosis (DF) is a pathological intermediate fibroblastoma that is difficult to control locally due to its invasive nature, especially in the extremities.Although anlotinib demonstrated efficacy in treating DF with tolerable safety, the impact of surgical intervention in conjunction with anlotinib administration on local control in patients with extremity DF remains undetermined. Methods: We conducted a retrospective examination of the clinical medical documentation belonging to patients with resectable DF of the extremities who were treated with surgery between January 2010 and June 2022. The patients were divided into two cohorts: surgery alone cohort and surgery combined with anlotinib group (surgery plus anlotinib cohort), crossover to surgery plus anlotinib cohort was admissible for patients in the surgery alone cohort who experienced disease recurrence postoperatively. Clinical data such as basic information, tumor location, anlotinib toxicity, time to recurrence, surgical complications, follow-up time, visual analogue scale (VAS) score and Musculoskeletal Tumor Society (MSTS) score at the last follow-up were collected. Results: In total, 48 consecutive patients (19 males and 29 females) with resectable DF of the extremities, including 25 patients in the surgery alone cohort, 23 patients in the surgery plus anlotinib cohort, and 10 patients who were transferred from the surgery alone cohort to the surgery plus anlotinib cohort. The VAS score at the last follow-up was 5 (IQR,(3)(4)(5)(6) in the surgery alone cohort and 2 (IQR, 1-3) in the surgery plus anlotinib cohort, respectively; the MSTS score at the last follow-up was 19 (IQR, in the surgery alone cohort and 27 (IQR,(25)(26)(27)(28) in the surgery plus anlotinib cohort, respectively; these characteristics were statistically different between the two cohorts. The 3-year recurrence-free survival (RFS) of the surgery alone cohort and the surgery plus anlotinib cohort were 37.7% and 72.6%, respectively, and the difference was statistically significant (p = 0.022). Conclusions: Surgery combined with anlotinib appears to be effective in controlling local recurrence in patients with resectable DF of the extremities, and the side effects were acceptable.